2021
DOI: 10.1049/nbt2.12063
|View full text |Cite
|
Sign up to set email alerts
|

Design of 3‐aminophenol‐grafted polymer‐modified zinc sulphide nanoparticles as drug delivery system

Abstract: Zinc sulphide (ZnS) nanoparticles were synthesized by the coprecipitation method. The ZnS nanoparticle surface was polymerized with allyl glycidyl ether (AGE), and 3aminophenol was then deposited as a ligand on nanosorbent. The modified nanosorbent was investigated with Fourier transform infrared spectroscopy and thermogravimetric analysis. The particle size of the modified nanosorbent was studied with scanning electron microscopy. Some characteristic factors of the adsorption process such as pH and time were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Dubinin–Radushkevich model was applied to understand the Hg 2+ sorption type. This type is a form of empirical isotherm and it is expressed the Gaussian energy distribution by adsorbate sorption mechanism on a heterogeneous surface and a linear model is given as [40, 41]: In0.16emqebadbreak=In0.16emqDgoodbreak−BDfalse(In0.16emRT(1+1/Ce)false)2$$\begin{equation}In\,{q_e} = In\,{q_D} - {B_D}{(In\,RT(1 + 1/{C_e}))^2}\end{equation}$$…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dubinin–Radushkevich model was applied to understand the Hg 2+ sorption type. This type is a form of empirical isotherm and it is expressed the Gaussian energy distribution by adsorbate sorption mechanism on a heterogeneous surface and a linear model is given as [40, 41]: In0.16emqebadbreak=In0.16emqDgoodbreak−BDfalse(In0.16emRT(1+1/Ce)false)2$$\begin{equation}In\,{q_e} = In\,{q_D} - {B_D}{(In\,RT(1 + 1/{C_e}))^2}\end{equation}$$…”
Section: Methodsmentioning
confidence: 99%
“…Dubinin-Radushkevich model was applied to understand the Hg 2+ sorption type. This type is a form of empirical isotherm and it is expressed the Gaussian energy distribution by adsorbate sorption mechanism on a heterogeneous surface and a linear model is given as [40,41]:…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…Such observations demonstrated that accessibility of empty Fe 3 O 4 @MWCNT-CN binding sites at initial stages of dye adsorption and after that equilibrium is reached, occupying other empty sites would be difficult. This is reasoned by the repellent forces between the bromocresol green molecules and Fe 3 O 4 @MWCNT-CN [31,32].…”
Section: Factors Influencing the Measurement Of Dye Extractionmentioning
confidence: 99%
“…At this stage, the experimental data on adsorption equilibrium with Freundlich, Langmuir, and Temkin isotherms were examined. The equations for isotherm models of Langmuir, Temkin, and Freundlich are as follows, respectively [47, 48]. Ceqe=1Q0b+CeQ0 qe=BlnkT+BLnCe logqe=logKf+1nlogCe where Q 0 is the highest antimony ions sorption capacity at Fe@Mg‐Al LDH (mg/g) and b is the constant of the Langmuir Equation (L/mg), k T (L/g) and B (J/mol) are the constants of the Temkin Equation, K f ((mg/g)·(L/mg) 1/ n ) and n are the constants of the Freundlich Equation, C e (mg/L) is the concentration of the adsorbate in the liquid phase after reaching equilibrium, and q e (mg/L) is the amount of the adsorbate per unit mass of Fe@Mg‐Al LDH [49].…”
Section: Resultsmentioning
confidence: 99%
“…At this stage, the experimental data on adsorption equilibrium with Freundlich, Langmuir, and Temkin isotherms were examined. The equations for isotherm models of Langmuir, Temkin, and Freundlich are as follows, respectively [47,48].…”
Section: Study Of Isothermsmentioning
confidence: 99%